2008
DOI: 10.1111/j.1467-8624.2008.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Postural and Object‐Oriented Experiences Advance Early Reaching, Object Exploration, and Means–End Behavior

Abstract: The effects of 3 weeks of social (control), postural, or object-oriented experiences on 9- to 21-week-old infants' (N = 42) reaching, exploration, and means-end behaviors were assessed. Coders recorded object contacts, mouthing, fingering, attention, and affect from video. Postural and object-oriented experiences advanced reaching, haptic exploration of objects, and developing means-end behavior compared to social experience. Object-oriented experience best-advanced means-end behavior. The results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
128
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 111 publications
(233 reference statements)
4
128
1
1
Order By: Relevance
“…The act of grasping the object per se typically comes later, when infants have figured out how to make hand-toy contact (von Hofsten & Lindhagen, 1979). A recent study by Lobo and Galloway (2008) is consistent with such an explanation. These researchers found that pre-reaching infants who received a similar "grasping" experience did not explore objects much until after the onset of reaching -that is, when they were successful at touching the toy.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The act of grasping the object per se typically comes later, when infants have figured out how to make hand-toy contact (von Hofsten & Lindhagen, 1979). A recent study by Lobo and Galloway (2008) is consistent with such an explanation. These researchers found that pre-reaching infants who received a similar "grasping" experience did not explore objects much until after the onset of reaching -that is, when they were successful at touching the toy.…”
Section: Discussionmentioning
confidence: 77%
“…Another key way infants select successful reaching movements is through repeated experience and exposure to the reaching-specific context which allows for active reaching attempts toward objects, exploration of the properties and consequences of their arm movements, and selection of those movements that prove to be the most successful, or valuable. As these contemporary theoretical perspectives emerged, investigations into the effects that different types of sensorymotor experiences have on the formation of new forms of behavior have become increasingly popular (Bojczyk & Corbetta, 2004;Libertus & Needham, 2009, 2010Lobo & Galloway, 2008;Lobo, Galloway, & Savelsbergh, 2004;Needham, Barrett, & Peterman, 2002). These studies show in different ways that particular types of sensory-motor experiences can influence the way infants interact with objects and affect the formation of goal-directed behaviors and developmental trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…Coding reliability was assessed on 20% of the visits, with an agreement of 80.2% for hands to midline and 91.8% for hand contact. 13 The Early Problem Solving Indicator (EPSI), the cognitive portion of the Individual Growth and Development Indicators (IGDI), 21 was used to assess play-based problem solving during infant-directed play. The IGDI developers certified the EPSI coder as a reliable coder for the EPSI with greater than 85% agreement with master coders.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…10,11 Although some studies have challenged current practice patterns, families of infants born preterm are not routinely provided with information or recommendations on why and how to provide early experiences in the first months of life. 6,7,[12][13][14] Delaying intervention limits the amount of intervention provided during a critical window for altering neural pathways and likely reduces the efficacy of EI on motor development. 3,10,15 Supporting Play Exploration and Early Development Intervention (SPEEDI) is an intervention that blends the need for early and intense intervention with family support to engage families in their child's development during transition from the NICU to home and the community.…”
Section: Introductionmentioning
confidence: 99%
“…Video recordings were reviewed by a coder who was blinded to the purpose of the study. Intra-rater reliability was established at >90% for this coder for 20% of the data using the equation: [agreed/(agreed + disagreed)] × 100 (Angulo-Kinzler & Horn, 2001;Harris & Lahey, 1978;Lobo & Galloway, 2008). The coder used MacSHAPA behavioral coding software to review the videos and code for instances and durations of each behavior.…”
Section: Methodsmentioning
confidence: 99%